A separação dos poderes: uma reflexão à luz da decisão judicial, do normativismo concreto de Miguel Reale e da problemática do valor - Soares, Gabrielle Valeri (2022)
This dissertation proposes to analyze, without pretense of exhaustion of the theme, Montesquieu's Theory of the Tripartition of Powers (and its respective updates), the theories of judicial decision-making (notably with notes referring to Hart, Dworkin and Alexy) and Miguel Reale's Three-Dimensional Theory of Law, in which special attention will be given to concrete legal normativism and the question of value, from the perspective of the philosophy of law. It is also intended to briefly expose the historical evolution of constitutionalism. The methodology used comprises a qualitative, dialectical approach, of a basic nature, containing an explanatory objective and a bibliographic, documentary, historical and observational procedure. The results of the research carried out indicate that: (i) there is the possibility of outlining a dialogue between Miguel Reale's concrete normativism and the theories of judicial decision of Dworkin and Alexy; (ii) depending on the judicial decision model adopted, the way of understanding the operation of the separation of powers changes; (iii) it is possible to trace a correlation between the proper functioning of the separation of powers and the preservation of constitutional democracy; (iv) the Federal Constitution of 1988 brings together a set of principles that, in the axiological plane, correspond to values, which oblige by virtue of representing, according to Miguel Reale, man himself (a spiritual self-awareness) and (v) the Federal Constitution of 1988 can be seen as guardian of the fundamental value of the dignity of the human person, as provided in its article 1, item III